2015
DOI: 10.4085/1062-6050-50.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Using Accelerometer and Gyroscopic Measures to Quantify Postural Stability

Abstract: Context: Force platforms and 3-dimensional motion-capture systems provide an accurate method of quantifying postural stability. Substantial cost, space, time to administer, and need for trained personnel limit widespread use of biomechanical techniques in the assessment of postural stability in clinical or field environments.Objective: To determine whether accelerometer and gyroscope data sampled from a consumer electronics device (iPad2) provide sufficient resolution of center-of-gravity (COG) movements to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 51 publications
3
86
0
2
Order By: Relevance
“…Secondly, no motion capture or force platform system was incorporated into this study. However, 95EV, derived from a lumbar-mounted accelerometer and gyroscope has previously been compared to force platform and 3D motion capture systems [20]. Alberts et al [20] demonstrated that during components of the balance error scoring system, the kinematic data obtained from an iPad embedded inertial sensor are of sufficient quality relative to motion capture data to accurately quantify static balance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, no motion capture or force platform system was incorporated into this study. However, 95EV, derived from a lumbar-mounted accelerometer and gyroscope has previously been compared to force platform and 3D motion capture systems [20]. Alberts et al [20] demonstrated that during components of the balance error scoring system, the kinematic data obtained from an iPad embedded inertial sensor are of sufficient quality relative to motion capture data to accurately quantify static balance.…”
Section: Discussionmentioning
confidence: 99%
“…However, 95EV, derived from a lumbar-mounted accelerometer and gyroscope has previously been compared to force platform and 3D motion capture systems [20]. Alberts et al [20] demonstrated that during components of the balance error scoring system, the kinematic data obtained from an iPad embedded inertial sensor are of sufficient quality relative to motion capture data to accurately quantify static balance. Additionally, the repeated pre-fatigue baseline testing points demonstrated the relatively low levels of within-subject variability across the 3 time points, indicating its relative stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such systems address some of the aforementioned limitations of traditional motion capture, as they allow for inexpensive, accessible quantification of human movement, in an unconstrained environment (Giggins et al, 2013). These IMU systems have been used in the objective quantification of a range of activities, from static balance tasks (King et al, 2014, Alberts et al, 2015, Furman et al, 2013, to dynamic tasks such as the squat and single leg squat , walking (Zijlstra andHof, 2003, Yang et al, 2013) and running (Lee et al, 2010). Early work investigating the use of IMUs in balance assessment has shown that a static balance assessment, instrumented with an IMU mounted on the lumbar spine, was not as effective as the traditional subjectively scored assessment in identifying balance deficits post-concussion (Furman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%